2012
DOI: 10.1016/j.jhydrol.2012.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Response of deep soil moisture to land use and afforestation in the semi-arid Loess Plateau, China

Abstract: s u m m a r ySoil moisture is an effective water source for plant growth in the semi-arid Loess Plateau of China. Characterizing the response of deep soil moisture to land use and afforestation is important for the sustainability of vegetation restoration in this region. In this paper, the dynamics of soil moisture were quantified to evaluate the effect of land use on soil moisture at a depth of 2 m. Specifically, the gravimetric soil moisture content was measured in the soil layer between 0 and 8 m for five l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
132
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 215 publications
(143 citation statements)
references
References 46 publications
10
132
1
Order By: Relevance
“…6 indicated that soil-water regimes depended highly on the plant species of the land-use patterns. The AW in the farmland was the highest, followed by grassland, and the AW in S was the lowest; this trend was consistent with the results of Yang et al (2012) whose SWC data was based on a 0-800 cm soil profile (which may reflect plant-root development to some extent). AW in the mixed land-use patterns was in the order S-O > S-G > S-Alf.…”
Section: Overall Distribution Of Soil Watersupporting
confidence: 88%
See 2 more Smart Citations
“…6 indicated that soil-water regimes depended highly on the plant species of the land-use patterns. The AW in the farmland was the highest, followed by grassland, and the AW in S was the lowest; this trend was consistent with the results of Yang et al (2012) whose SWC data was based on a 0-800 cm soil profile (which may reflect plant-root development to some extent). AW in the mixed land-use patterns was in the order S-O > S-G > S-Alf.…”
Section: Overall Distribution Of Soil Watersupporting
confidence: 88%
“…Considerable interest has since been generated around the world in the assessment of vertical distribution and influencing factors Yang et al, 2012), depletion and replenishment (Li and Huang, 2008;Liu et al, 2010), dynamics and simulations (Jipp et al, 1998;Markewitz et al, 2010;Zhao et al, 2008) of SWC in soils to a depth of roughly 1000 cm. The depth of depletion of SWC, inferred to be a function of root uptake, has recently been reported to be 1800 cm in an Amazonian forest (Davidson et al, 2011) and to be 1550, 2240 and 2150 cm (based on the comparison of soil-water conditions between shrublands/forests and permanent farmland) in alfalfa grassland, Caragana korshinskii shrubland and pine forest, respectively, on the Loess Plateau of China (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike native plants, introduced vegetation usually has a higher water demand and annual rainfall levels cannot supply sufficient water for growth (Chen et al, 2008a;Wang et al, 2010). Introduced plants in this region are thus forced to develop deep and robust root systems to utilize soil moisture in deep soil layers (Chen et al, 2008a;Yang et al, 2012a). The limited water stored below the surface layers has become a particularly important component of ecosystems in this region.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on land use change and its impacts on catchment hydrology is extensive, with studies examining the effects of (1) conversion to agricultural land use (Thanapakpawin et al, 2007;Warburton et al, 2012); (2) deforestation (Costa et al, 2003;Coe et al, 2011); (3) afforestation (e.g., Yang et al, 2012;Brown et al, 2013) and (4) urbanization (Bhaduri et al, 2001;Rose and Peters, 2001). Fewer studies have examined how traditional modeling approaches must be modified to handle nonstationary conditions, or how modeling methods can be used to assess impacts of land use change.…”
Section: Introductionmentioning
confidence: 99%